Perioperative ultrasound screening of lower extremity veins is effective in the prevention of fatal pulmonary embolism in orthopedic patients - Haoran Li; Zhi Li; Na Yang; Jian Xing; Huijun Yuan; Zhe Song; Xing Wei; Teng Ma; Qian Wang; Pengfei Wang; Kun Zhang (Scientific Reports)
Abstract Patients at high risk of deep vein thrombosis are recommended to undergo lower-extremity ultrasonography to screen for pulmonary embolism (PE); however, there are few reports on whether this can effectively reduce the occurrence of fatal pulmonary embolism (FPE). This study aimed to assess the risk factors associated with PE and to investigate whether perioperative ultrasound screening of lower extremity veins in orthopedic patients can effectively reduce the incidence of FPE. We enrolled 137 patients with PE who underwent orthopedic surgery between 2013 and 2020. Patients were divided into survival and non-survival groups based on whether FPE occurred during hospitalization. Demographic and clinical data were compared between groups. Ultrasound screening was effective in reducing the incidence of FPE in orthopedic patients. Thrombolytic therapy and computed tomography pulmonary angiography (CTPA) were highlighted factors that protect against FPE. Coronary heart disease was found to be independent risk factors for FPE. Proximal thrombus associated with an FPE. Ultrasound screening of the lower limb veins should be routinely performed in orthopedic patients during the perioperative period. Prophylactic inferior vena cava filter implantation, thrombolytic therapy, and CTPA can be performed in patients with suspected PE to reduce its incidence.